Bilateral vocal cord immobility resulting from cytomegalovirus pharyngitis: A case report. Issue 2 (February 2018) - Ueha, Rumi; Nito, Takaharu; Goto, Takao; Sato, Taku; Ushiku, Tetsuo; Yamasoba, Tatsuya
Abstract: Human cytomegalovirus (CMV) is an infectious herpes virus present in approximately 50% of the world's population. Pharyngitis is an uncommon manifestation of CMV infection, and vocal cord immobility (VCI) following CMV pharyngitis is quite rare. An 83-year-old man with well-controlled diabetes mellitus and hypertension was admitted due to dyspnea, odynophagia, and dysphagia. Laryngeal fiberscopy revealed bilateral vocal cords almost fixed at the median position, with mucosal redness, swelling, and edema at the hypopharyngeal area. The airway was so narrowed that an emergency tracheostomy was performed to secure an airway. VCI resulting from a malignant tumor was suspected at first, but repeated pathological examinations revealed CMV infection in the pharyngeal mucosa. Despite intravenous ganciclovir treatment (5 mg/kg), the patient's bilateral VCI improved only slightly. Laryngeal electromyography was used to investigate the causes of VCI, and revealed vocal fold paralysis on the left side and cricoarytenoid joint fixation on the right side. This case highlights the importance of considering CMV infection in the differential diagnosis of patients with pharyngitis and VCI. To the best of our knowledge, this is the first case report describing the etiology of VCI following CMV pharyngitis using laryngeal electromyography.